2008
DOI: 10.1373/clinchem.2007.098731
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Search for Placental DNA-Methylation Markers on Chromosome 21: Toward a Maternal Plasma-Based Epigenetic Test for Fetal Trisomy 21

Abstract: BACKGROUND:The presence of fetal DNA in maternal plasma represents a source of fetal genetic material for noninvasive prenatal diagnosis; however, the coexisting background maternal DNA complicates the analysis of aneuploidy in such fetal DNA. Recently, the SERPINB5 gene on chromosome 18 was shown to exhibit different DNA-methylation patterns in the placenta and maternal blood cells, and the allelic ratio for placenta-derived hypomethylated SERPINB5 in maternal plasma was further shown to be useful for noninva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 24 publications
3
108
1
5
Order By: Relevance
“…Recently, a number of approaches have been developed. One strategy targets a fetal-specific subset of nucleic acids in maternal plasma, e.g., placental mRNA (9)(10)(11) and DNA molecules bearing a placental-specific DNA methylation signature (12)(13)(14). The fetal chromosomal dosage is then assessed by allelic ratio analysis of SNPs within the targeted molecules.…”
Section: Down Syndrome ͉ Solexa Sequencing ͉ Trisomy 21mentioning
confidence: 99%
“…Recently, a number of approaches have been developed. One strategy targets a fetal-specific subset of nucleic acids in maternal plasma, e.g., placental mRNA (9)(10)(11) and DNA molecules bearing a placental-specific DNA methylation signature (12)(13)(14). The fetal chromosomal dosage is then assessed by allelic ratio analysis of SNPs within the targeted molecules.…”
Section: Down Syndrome ͉ Solexa Sequencing ͉ Trisomy 21mentioning
confidence: 99%
“…Different fetal (placental) and maternal methylation of regions on chromosome 21 were tracked for the purposes of Down Syndrome non-invasive prenatal diagnostics. Different methylation showed 22 out of 114 assessed genomic regions on this chromosome (Chim et al, 2008). This relatively large number of methylation specific fetal DNA sequences offers a promising source of prenatal biomarkers independent on maternal and fetal genotype.…”
Section: Noninvasive Down Syndrome Diagnostics By Cffdna Epigenetic Dmentioning
confidence: 94%
“…Moreover, it was demonstrated that the methylation status for the sequences tested was not altered between early and term pregnancy [Old et al, 2007]. Recently, Chim et al have performed a systematic search of 114 studied genomic regions (CpG islands) on chromosome 21 in a search for loci that were differentially methylated in placental tissue and blood cells and identified 22 (19%) that showed epigenetic differences between the maternal and fetal tissues [Chim et al, 2008]. The next step was to propose two new fetal-DNA epigenetic markers, U-PDE9A and U-CGI137 found in the maternal circulation only during pregnancy and rapidly cleared upon delivery of the fetus [Chim et al, 2008].…”
Section: The Role Of Epigenetic Markers In Rapid Detection Of Down Symentioning
confidence: 99%
“…Recently, Chim et al have performed a systematic search of 114 studied genomic regions (CpG islands) on chromosome 21 in a search for loci that were differentially methylated in placental tissue and blood cells and identified 22 (19%) that showed epigenetic differences between the maternal and fetal tissues [Chim et al, 2008]. The next step was to propose two new fetal-DNA epigenetic markers, U-PDE9A and U-CGI137 found in the maternal circulation only during pregnancy and rapidly cleared upon delivery of the fetus [Chim et al, 2008]. This research group used a high resolution approach via bisulphite sequencing that increased the number of applicable CpG sites by 5-fold compared with the abovementioned HpaII-based approach.…”
Section: The Role Of Epigenetic Markers In Rapid Detection Of Down Symentioning
confidence: 99%